Kajian terhadap pengamalan pengurusan penyenggaraan oleh industri terpilih di Malaysia - Omain, Siti Zaleha (2000)
The drastic development of the industrial sector in Malaysiacauses maintenance to be more significant in its importance becasse of, amongothers, the increaseduse of sophisticatedmachinery and equipment. No study has been done to look into the practices of maintenance in industriesin Malaysia. Therefore,this thesis aims to get information of the types of maintenance used by some major industries in Malaysia, namely; Electricaland Electronics(E&E), Wood and Wood Products(p&PP) and Transport and Transport Equipment(PG&PPG). This requires that the importantfactor in an ideal maintenance management systemsbe determined. These factors are; the commitment of the management, equipment ownership, support from other departments in maintenance, continuous improvement, smallgroup activities, teamwork, training and education, planned maintenance, autonomous maintenance, levels of usage and lastly maintenance record keeping. The questionnaire constructedbased on these factors were then distributed to companiesidentified. The results of the study show that there are differences in the practices of the maintenance systems between smalland large companies in the above three industries. There is no significance difference betweensmall and large companies in practisingthe ideal maintenance management components in all three industries. However, there exists significant difference among large companiesin all the three industries. As a whole, the practice of the idealmaintenance management components in companieswithinthe selected industries is consideredto be average except large companiesin the E&E industry.